2015
DOI: 10.3329/icpj.v4i2.21484
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and hypolipidemic potential of Rhazya stricta Decne extract and its fractions

Abstract: Diabetes mellitus is the most common human disease and there is growing interest for plant based therapy in managing diabetes mellitus specifically in the developing world. In the present study, Rhazya stricta Decne extract was analysed for its antidiabetic activities. Crude methanolic extracts of different plant parts were tested in vivo on albino mice Balb-C, for the reduction of blood glucose, urea, cholesterol, triacylglycerides and glycosylated haemoglobin. Results obtained showed that leaves of R. strict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
(6 reference statements)
1
9
0
Order By: Relevance
“…Continuous monitoring of the blood glucose levels of diabetic patients and HBA1C levels are considered important factors in the treatment of DM. The root extracts of R. stricta considerably reduced the blood glucose level and HbA1c in accordance with previous reports where aerial parts of the plant were seen reducing blood glucose levels and HbA1c accordingly [13,14]. Another study reported that long-term oral administration of alkaloids rich fractions of R. stricta significantly improved the insulin level and insulin resistance which showed insulin secretagogue activity of the plant for the disposal of blood glucose [16].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Continuous monitoring of the blood glucose levels of diabetic patients and HBA1C levels are considered important factors in the treatment of DM. The root extracts of R. stricta considerably reduced the blood glucose level and HbA1c in accordance with previous reports where aerial parts of the plant were seen reducing blood glucose levels and HbA1c accordingly [13,14]. Another study reported that long-term oral administration of alkaloids rich fractions of R. stricta significantly improved the insulin level and insulin resistance which showed insulin secretagogue activity of the plant for the disposal of blood glucose [16].…”
Section: Discussionsupporting
confidence: 89%
“…The outcome of these biochemical parameters pointed out lipid-lowering potential and beneficial effects of the root extract on kidneys and liver functions of the mice. The extract of the leaves of R. stricta was reported in lowering the levels of cholesterol and triglycerides in animals [13,14,16,66]. The histological examination of the mice liver has shown that the administration of the root extract fractions has not posed any substantial alterations of liver cells and any kind of known hepatic variations like dilation, congestion, necrosis or hypertrophy were not seen in all treated groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But these two sister species exhibit similarity in possessing therapeutically significant secondary metabolites. About 100s of alkaloids [2] and flavonoids from R. stricta contain innumerable pharmacological properties [5] [6] [7]. R. stricta is considered as a potential chemopreventive [8] [9], antifungal [10], and antidiabetic [11] agent and also produces analgesic and sedative effects [7].…”
Section: Introductionmentioning
confidence: 99%
“…About 100s of alkaloids [2] and flavonoids from R. stricta contain innumerable pharmacological properties [5] [6] [7]. R. stricta is considered as a potential chemopreventive [8] [9], antifungal [10], and antidiabetic [11] agent and also produces analgesic and sedative effects [7]. Likewise the metabolites originating from R. orientalis have various anti-cancer and anti-tumor properties [12].…”
Section: Introductionmentioning
confidence: 99%